Determinants of Employment in the Ministerial Bureaucracy - Thomas Braendle (University of Basel, Center of Business and Economics (WWZ), 2012)
Senior officials in the ministerial bureaucracy are responsible for the coordination of public service activity and their number has grown enormously since World War II. We study the growth in employment of this politically sensitive high-profile occupational group from a political economics perspective. We analyze how political partisanship, political patronage after changes in government, and the selection of public servants into politics affect senior official employment. Based on a unique time-series, cross-sectional data set for the German Laender, we find mixed evidence for the effect that the political selection of public servants has on senior official employment. We find some evidence for political patronage.
Keywords: D72; D73; H11; H72; 330; political selection; public servants; public-sector growth; bureaucracy; patronage; Bürokratie; Öffentlicher Dienst; Patronage; Teilstaat; Deutschland